Towards an agential realist concept of learning. Issue 4 (December 2018) - Plauborg, Helle
Abstract This article develops an agential realist concept of learning by thinking through existing learning theory and some of the discussions I consider essential in the field. Based on an excerpt from a field note, central concepts such as acquisition and transfer are rethought and the argument is made that intra-activity and 'leaps' are characteristic aspects of learning. Reconfigurations are seen as pivotal for this way of thinking about learning and break with the tendency to understand learning as either more of the same or as radical change. Finally, I relate the concept of learning developed in the article to other posthuman understandings of learning and discuss the contribution of agential realism.